Efficacy of the SMARTV3UMS learning management system in art and design courses - Lee, Lilian Shiau Gee; Victor Pangayan (International Journal of Learning, Teaching and Educational Research, 2022)
Educational institutions are developing e-learning that uses intervention and individual interaction in the learning process to become more efficient and successful. Learning management systems (LMSs) aid in the management of teaching components and online contact between teachers and students. However, their effectiveness is highly dependent on a thorough understanding of the obstacles and factors that influence their use among their users. This relates in particular to transferability and knowledge acquisition among students, especially those enrolled in art and design majors. The purpose of this study was to investigate the effects of knowledge management (KM) on the SMARTV3UMS learning system for art students. SMARTV3UMS is an LMS system that all art students at Universiti Malaysia Sabah must use during their courses. A quantitative survey was undertaken to assess knowledge acquisition, sharing, application, protection, internalization, and creation in relation to the SMARTV3UMS system and user experience. Descriptive and inferential statistics were used to analyze the collected data and assess the study objectives. In SMARTV3UMS, knowledge acquisition, internalization, and creation were the three KM components most adopted by the participating 216 art students. Gender and geographic area did not affect the SMARTV3UMS “fit” quality measures for student KM. The findings revealed that KM creates diverse instructional techniques and alters the learning process in e-learning. Stakeholders can assess student thinking, experience, and knowledge of educational technology use by evaluating the KM domain. SMARTV3UMS needs a solid KM integration strategy and a plan to support learning, specifically online art and design learning, as well as visual arts students’ e-learning implementation concerns.